A systematic literature review about team diversity and team performance: Future lines of investigation - Lurdes Patrício; Mário Franco (Administrative Sciences, 2022)
This study aims to identify the different research paths that help us understand the emerging aspects explaining how team diversity influences team performance. We also present future lines of investigation that could help us to understand this theme. The study is a systematic literature review (SLR) of articles collected from the Web of Science (WoS) database, within management or business categories, published between 1996 and 2020, considering knowledge diversity, team heterogeneity, team wisdom, cross-functional project teams, and team composition. This study enables the systematization of the existing literature. The framework presented is based on the reviewed articles and explains the articulation of the concepts of team diversity and team performance based on three literature clusters, namely: (1) Team Knowledge Diversity, (2) Diversity Effects and (3) Desirable Outcomes of Diversity. Therefore, this work enriches the systematization of the academic literature on this topic, providing an original framework and a future research agenda organized by literature cluster.
Keywords: 350; knowledge diversity; systematic literature review; team diversity; team heterogeneity